PERSONAL BRANDING SEBAGAI KOMODIFIKASI KONTEN PADA AKUN YOUTUBE RAHMAWATI KEKEYI PUTRI CANTIKA - NADIALISTA KURNIAWAN; SONIA GABRIELLA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study describes how personal branding by Youtuber Rahmawati Kekeyi Putri Cantika, which is currently being viral in Indonesian society, can become a commodification of contents a form of digital commercialization. Youtube was chosen as a digital commercialization media that provides space for content creators to create content that is in accordance with their personal branding, viewed from the perspective of political economy revealed by Vincent Mosco. This type of research uses the type of qualitative description, where researchers describe or construct a case study and look at a phenomena and examine a condition, results of thinking about events that occur. The results of this study indicate that the creation of personal branding created by Kekeyi has fulfilled eight elements as revealed by Peter Montoya (2002), reflected through analysis in each of Kekeyi's Youtube video categories, which is then utilized as a commercialization of commercialized content and obtained fantastic profits for Kekeyi herself.